Desmoid Tumor Patients Profile in Dr. Soetomo Surabaya Hospital: A Rare Event - Meidini Rahmat, Beatta; Danardono, Edwin; Wihandono, Asdi (Jurnal Health Sains, 2025)
Desmoid tumor (DT) is a fibroblast soft tissue tumor that deep seated connective tissue malignancy developing in musculoaponeurtic tissues. Desmoid tumor is a rare tumor, reported 5-6 cases per million population and account 0.03% of all neoplasm yet the etiopathogenesis of this tumor remains unclear. DT most commonly develops between the age of 15-60 years and common in females, although it rarely metastasized but locally aggressive and affect the adjacent structures. Knowing the profile of desmoid tumor patients at RSUD Dr. Soetomo Surabaya for the period January 2020 – December 2024. Including demographic patients, risk factors, tumor sites, and patients’ managements. All patients between January 2020-December 2024 whose primary DTs were observed. Datas were obtained and observational descriptive study conducted from medical files to record patient’s age, sex, tumor site, and therapeutic managements. All 16 patients were obtained during 5 years with female predominantly (1:4) and adult was more common 19-44 years. Risk factors including in this study were history of trauma, history on pregnancy, and hormonal contraceptive. Location of tumors were found mostly in abdominal wall and the therapy conducted were surgery followed by chemotherapy, and combination of hormonal therapy, TKIs, and radiotherapy. DT is a rare fibroblastic neoplasm that shows locally aggressive behavior with very low incidence annually with female, history of trauma, history of pregnancy, and hormonal contraceptive as a major risk factors. The therapeutic management includes multidisciplinary approach.